DEPARADOXING CONSTITUTIONAL DEMOCRACY. - CLAUS, LAURENCE (NLUJ, 2025)
Democracy can become more fragile as it becomes more complete. Socrates noticed this paradox three millennia ago. British parliamentary and American presidential systems of government established stable electoral patterns during the long formative periods when those systems were not as democratic as they are today. Elitist ways of selecting legislators stopped even the most popular prime ministers and presidents from fully controlling Parliament and Congress. When these systems have been emulated elsewhere with mass voting from the outset, they have often failed. Fuller democracy can enable a charismatic leader to transform a mass following into a disciplined party that can exploit transient popularity to control legislatures and turn democracy against itself. But this paradox is resolvable. Comparative constitutional experience shows that we can be fully democratic today and reliably stay fully democratic tomorrow by redesigning the way we vote for legislators and the way we structure executives.